Socio-Economic Status Determines Risk of Receptive Syringe Sharing Behaviors among Iranian Drug Injectors; A National Study - Assari, Shervin; Ahmadi, Khodabakhsh; Rezazade, Majid (Frontiers in Psychiatry, 2015)
Background: Although needle and syringe sharing is one of the main routs of transmission of HIV in several countries in the middle east, very little is known about how socio-economic status of injecting drug users (IDUs) is linked to the receptive syringe sharing behaviors in these countries. Aim: To study socio-economic correlates of receptive needle and syringe sharing among IDUs in Iran. Methods: The study used data from the Unhide Risk Study, a national survey of IDUs. This study sampled 636 IDUs (91% male) via snowball sampling from eight provinces in Iran in 2009. Socio-demographic and drug use characteristics were collected. We used a logistic regression to determine factors associated with receptive needle and syringe sharing during the past 6 months. Results: From 636 IDUs enrolled in this study, 68% (n = 434) reported receptive needle and syringe sharing behaviors in the past 6 months. Odds of receptive needle and syringe sharing in the past 6 months was lower among IDUs who were male [odds ratios (OR) = 0.29, 95% confidence interval (CI) = 0.12–0.70], had higher education (OR = 0.74, 95% CI = 0.64–0.86) but higher among those who were unemployed (OR = 4.05, 95% CI = 1.50–10.94), and were single (OR = 1.47, 95% CI = 1.02–2.11). Conclusion: This study presented factors associated with risk of receptive needle and syringe sharing among Iranian IDUs. This information may be used for HIV prevention and harm reduction purposes. Socio-economic status of Iranian IDUs may be closely linked to high-risk injecting behaviors among them.